The Role of Emotional Intelligence in Mediating the Influence of Work-Family Conflict and Work Environment on Job Performance of Female Police Personnel of the Southeast Sulawesi Regional Police (Architecture Image Studies, 2025)
The purpose of this study is to test and examine the role of emotional intelligence in mediating the influence of work-family conflict and work environment on job performance in Polwan Personnel of the Southeast Sulawesi Regional Police. The collection and respondents of this study were all Polwan Personnel of the Southeast Sulawesi Regional Police, totaling 126 people. The analysis tool used was SmartPLS. The results of the study indicate that work-family conflict has a negative and significant effect on emotional intelligence. Work-family conflict has a negative and significant effect on job performance. The work environment has a positive and significant effect on emotional intelligence. The work environment has a positive and significant effect on job performance. Emotional intelligence has a positive and significant effect on job performance. Emotional intelligence does not mediate the effect of work-family conflict on job performance. Then emotional intelligence mediates the effect of the work environment on job performance.